Increasing Artemia Cysts Production by Inoculating Nauplii into Hypersaline Lakes in Temperate Climate - Liudmila I. Litvinenko, Alexander I.Litvinenko, Elena G.Boiko, Marina A.Korendovych (International Journal of Advanced Science and Technology, 2020)
Years of monitoring the quantity of Artemia cysts in hypersaline lakes of Western Siberia showed that in lakes with salinity exceeding 150 g/ L, eggs and cysts predominated over live birth; therefore, the seasonal population dynamics declined significantly during the second and third generation of brine shrimps (July-August) (Litvinenko, Litvinenko &Boyko 2009; 2016). This seasonal dynamics feature of Artemia population was used for inoculating nauplii into the lake. Artemia cysts were incubated on the shore; incubation salinity was 50 g/ L, salinity in the lake was 130 g/ L. To overcome the saline shock, inoculation was performed during the first nauplial phase, when the intestines are not yet functioning. Preliminary calculation revealed this method would increase the cyst yield 9 times for of a single generation: 9 kgmay be obtained from 1 kg in 1-2 months.Keywords: Artemia culture, cyst production, salt lake.s